Deconstructing the history of Madioensche Kartinischool (1914–1919): Indigenous women's education in Madiun during the Dutch colonial period - Iqbal Rizki Sucahyo; Muhammad Syaifudin; Ilham Putra Pratama; Annisaa Khansa Labibah; Setia Ningrum; Ilzam Alzier Purbaya; Muhammad Najmudin bin Nadzri; Niswa Azmii Zameilani; Muhammad Faizzaby (Rafandha Press, 2026)
Background: During the colonial period, indigenous women faced severe marginalization in education due to restrictive traditional customs like pingitan and a lack of serious attention from the Dutch East Indies government. This situation began to shift in the early 20th century following the implementation of the Ethical Policy, which spurred humanists and local elites to establish specialized female educational institutions across Java. While major cities like Semarang have been widely researched, the historical development of such schools in smaller regions remains understudied. Purpose: This study aims to deconstruct the history of the Madioensche Kartinischool (Kartini School in Madiun) during its formative years from 1914 to 1919. It specifically examines its institutional origins, administrative dynamics, funding mechanisms, facilities, student body conditions, and curriculum development. Method: This study employs a qualitative approach with a historical research method consisting of five systematic stages: topic selection, heuristics (data gathering), verification (source criticism), interpretation, and historiography. Primary sources utilized include colonial archives, official annual reports (Jaarverslag) of the Vereeniging Madioensche Kartinischool (1916–1919), and contemporary photographs, complemented by relevant secondary literature. Findings: The school originated from a progressive local initiative under the